Efecto de la mezcla de los extractos crudos de ananas comosus y solanum melongena en rattus norvegisus var. albinus con hipercolesterolemia inducida” - Flores Effio, Karin Marisela (2008)
In the present study we demonstrated experimentally the effect of the mix of crude extracts of Ananas comosus and Solanum melongena in Rattus norvegicus var. albinus, which employs 24 specimens were grouped randomly into three groups. Each consists of eight animals, all three groups were induced hypercholesterolemia with lard liquid oral dose of 3.3mL/Kg body weight once a day for six weeks in addition to their usual diet. They were administered to groups II and III oral dose of 94.71 mg / kg b.w. and 189.42 mg / kg b.w. of the mixture of dry extract equivalent to 1mL and 2mL respectively of the mix of crude extracts of Ananas comosus and Solanum melongena for a period of four weeks. They took weekly blood samples for the determination of total cholesterol, HDL-cholesterol and LDL-cholesterol. While he was a statistically significant reduction in levels of cholesterol in groups II and III compared to the group I that did not receive treatment. Likewise, it was noted that a larger dose of the mixture of the extracts was found administered more hypocholesterolemic effect. This effect was due to the soluble fiber and phytoconstituents presence